Extracting Relevant Information Using Handheld Augmented Reality - Rehnuma Haque; Md. Mariful Islam; Sarmin Salma; Md. Abdullah Al Jubair; Ng, Giap Weng (2020)
Augmented Reality (AR) technology is being incorporated into education materials to attract students and to make the learning experience more engaging. This study focuses on the development of 3D object, audio-visual and interaction in Handheld AR. This research aims to bridge that gap using Handheld AR for a magazine, which allows students to get an overview and interact with the 3D model of the campus, view general information and events of the university. This magazine also benefits students that live outside Dhaka, who are unable to visit the campus beforehand. The users can use their Android phone camera for real-time video capture and render virtual objects in the augmented environment through Vuforia and Unity engine integration. To evaluate system effectiveness and user satisfaction, a survey is conducted. The survey consists of user background information, functionality tests and a user feedback questionnaire. The outcome of the survey shows satisfactory of the successful implementation of 3D and multimedia modules. This paper also discusses the future scopes and summarizes how to extract relevant information for students to gain knowledge and get entertainment by using handheld AR.